THE TYPE OF PHYSICAL ACTIVITY AS CENTRAL HEMODY-NAMIC MODULATION FACTOR - Pilipchuck, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The investigations of central hemodynamic indices in men with different physical activity level by tetrapole reovasographymethod were made. It has determined that in sportsmen stroke blood volume in 1,3 times and stroke index by 35 % higher that ones in non-sportsmen. At that time among long distance runners heart rate is in 1,4 times lower that point out to pronaunced bradicardia. The circulation minute volume indices didn’t have authentic differences in two groups. It has been emphasized that regular physical activity can economize heart function and prevent heart-vessels failure.